Validated High-performance Liquid Chromatography Method for Degradation Study of Ursodeoxycholic Acid and Silymarin: Validated High-performance Liquid Chromatography Method for Degradation Study of Ursodeoxycholic Acid and Silymarin - Sheikh, Imran A. (International Journal of Pharmaceutical & Biological Archive, 2018)
A novel and basic reversed-phase liquid chromatographic strategy has been set up for the determination of ursodeoxycholic corrosive and silymarin and studies its degradation pattern in pharmaceutical dosage forms. Ursodeoxycholic acid and silymarin are used to control Type 2 diabetes. The proposed work was performed on Young Lin (S.K) isocratic System UV Detector C18 column (150 mm Ã— 4.6 mm). A mixture of potassium phosphate, mobile phase in this method with a flow rate of 0.7 mL/ min (UV detection at 203 nm) and the method was validated as per the ICH guidelines. Forced degradation studies were performed by exposing the drug ursodeoxycholic acid and silymarin to acidic, alkaline, oxidation, and thermal stress degradations. The proposed reversed-phase-highperformance liquid chromatography technique was observed to be powerful and particular, and this strategy is reasonable for the measure of pharmaceutical dose frames and in addition kinetic examinations.